2011
DOI: 10.1182/blood-2010-12-326108
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD25+ T cells from hematopoietic stem cell grafts increases posttransplantation vaccine-induced immunity to neuroblastoma

Abstract: A multifaceted immunotherapeutic strategy that includes hematopoietic stem cell (HSC) transplantation, T-cell adoptive transfer, and tumor vaccination can effectively eliminate established neuroblastoma tumors in mice. In vivo depletion of CD4+ T cells in HSC transplantation recipients results in increased antitumor immunity when adoptively transferred T cells are presensitized, but development of T-cell memory is severely compromised. Because increased percentages of regulatory T (Treg) cells are seen in HSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…During immune priming, CD4 activity is dominated by helper function. Although it has been reported that CD4 cells are not required for priming, they are required for effective CD8 memory formation (32)(33)(34). CD8 memory cells formed in the absence of CD4 cells had an exhausted phenotype and increased PD-1 expression (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…During immune priming, CD4 activity is dominated by helper function. Although it has been reported that CD4 cells are not required for priming, they are required for effective CD8 memory formation (32)(33)(34). CD8 memory cells formed in the absence of CD4 cells had an exhausted phenotype and increased PD-1 expression (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials are underway investigating their therapeutic properties [166]. Targeting Tregs by anti-CD25 antibodies showed inhibition of neuroblastoma tumors in mice [167]. There are also data demonstrating that activation of the signal transducer and activator of transcription (STAT)3 signaling pathway supports tumor development by inducing accumulations of MDSCs and inhibition of DC differentiation [168]; hence its inactivation leads to inhibition of cancer development by a DC-and Treg-dependent mechanism [169].…”
Section: Molecular Targetsmentioning
confidence: 97%
“…In contrast to the multipronged vaccination strategy used here, those studies required tumor cell vaccination after de novo T-cell genesis following transplant, higher doses of donor T cells (.2.0 3 10 6 ), or presensitization of donor T cells with the tumor vaccine. [67][68][69] One objective of our study was to rapidly elicit T-cell responses by transplanted donor cells prior to de novo production of thymic-derived T cells. Expansion of donor tumor-reactive CD8…”
Section: Discussionmentioning
confidence: 99%